Determination of damage to undeletable and deletable windows of promising penetrators from the impact of high-speed regolith particles during impact penetration into the soil of the Moon - D. B. Dobriza; E. V. Leun (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article discusses promising penetrators with non-removable transparent and removable opaque windows, created mainly from corundum and ice composite, respectively. Their use will expand the scientific research program due to visualization capabilities for video recording of the movement of the penetrator in the subsurface layers of soil and their optical methods of studying, as well as direct contact with them. The calculation method and the calculated values of damage to these windows from the impact of spherical particles of lunar regolith with diameters of 1,0 and 1,5 mm, colliding with them at speeds of up to 1 km/s in the angular range from 70° to 80°, obtained using numerical modeling or based on an engineering model, are discussed.